Enhanced, hydrophobic, initial-shape programmable shape-memory composites with a bio-based nano-framework via gradient metal-ligand cross-linking. (22nd March 2022) - Wang, Xinghuo; Yang, Xueli; Xu, Chuanhui; Lin, Baofeng; Fu, Lihua
Abstract: Although thermal-responsive shape-memory composites (SMCs) have attracted more attention in advanced equipment and instruments as their shape changing characteristics stimulated by environmental signals, the repeated programming of the initial shape of SMCs remains a bottleneck. Herein, gradient metal-ligand cross-linking method is adopted to adjust the gradient distribution of thermoplastic carboxymethyl chitosan (CMCS)-Cu nano-framework in carboxyl styrene butadiene rubber (XSBR) matrix. One side, solid-state plasticity by metal coordination bond confers a permanent 2D and/or 3D shape configuration ability; Furthermore, the spatial-selective of metal ions can be controlled under a specific environment, which realizes the multiple reprogramming of the initial shape of the material. Meanwhile, the formation of CMCS-Cu nano-framework not only enhances the mechanical properties and Young's modulus of the composite (up to 20.5 and 170 MPa), but also endows it with excellent thermal-response sensitivity and solubility resistance. Based on the programmability and flexibility of the original shape, the material is made into human thermal response shape-memory bandage and applied to human fingers, showing the possibility of potential application as medical materials. This research provides a feasible strategy for the preparation of high-performance, hydrophobic and initial-shape reprogrammable SMCs based on bio-based materials. Graphical abstract: The osmotic cross-linking method is adopted to adjust the gradient distribution of the thermoplastic framework network in the rubber matrix. The formation of CMCS-Cu nano-framework not only realizes the 3D programming of the original shape in the cross-linking process, but also endows the initial shape of the material reprogrammed. Image 1 Highlights: A osmotic crosslinking method is adopted to adjust the gradient of CMCS-Cu in XSBR. Solid-state plasticity by CMCS-Cu confers a shape reconfiguration ability of SMCs. CMCS-Cu nano-framework greatly enhances the tensile properties and Young's modulus. CMCS-Cu nano-framework improves the thermal sensitivity and solubility resistance. The initial shape of SMCs are reprogrammable due to the dissociation effect of CMCS-Cu.